Recria de Rã touro (Rana catesbeiana) em tanques-rede alojados em viveiros de tilápia - Sousa, Rodrigo Morgado Ramalho de [UNESP]; Oliveira, Fernando Alcântara de [UNESP]; Argentim, Daniel [UNESP]; Wechsler, Francisco Stefano [UNESP]; Oliveira, Luciano Caetano de [UNESP]; Agostinho, Sueli Matiko Miyabara [UNESP]; Agostinho, Claudio Angelo [UNESP] (My University, 2010)
Brazilian systems for raising bullfrogs (concrete enclosure, concrete enclosure with feed dispenser and shelter, flooded enclosure) do not use enough water to keep temperature stable, and the low rate of water renewal hinders water quality. In this article we propose raising frogs in cages placed in fish ponds having high thermal stability. The experiment consisted in evaluating the productive performance of bullfrogs housed in 1 m3 cages at the densities of 28, 56 or 84 animals/ cage, fed a ration delivered by an automatic dispenser. Each pond was 72 m2 large. Two fish densities were used (200 or 300 tilapias/pond). The experimental period lasted 105 days for tilapias (May-August) and 60 days for frogs (July-August). No significant differences among densities were observed for frog performance. Using 200 tilapias/ pond improved fish weight gain and dissolved oxygen concentration, as compared to 300 tilapias/ pond. This new rearing system provided an adequate environment for frogs, as there was weight gain and zero mortality during winter.

No Brasil, os sistemas de criação de rãs (confinamento, anfigranja, inundado) utilizam um volume de água insuficiente para a manutenção da estabilidade térmica, e a baixa renovação prejudica a qualidade da água. Neste trabalho foi proposto a criação de rãs em tanques-rede distribuídos em viveiros com grande estabilidade térmica. O experimento consistiu em avaliar o desempenho produtivo de rãs-touro alojadas em tanques-rede de 1 m3, nas densidades de: 28, 56 e 84 animais por tanque-rede, alimentadas com ração fornecida por dispensador automático. Nos viveiros de 72 m2 utilizaram-se duas densidades de tilápias (200 e 300 peixes por viveiro). O período experimental foi de 105 dias para as tilápias (maio a agosto) e de 60 dias para as rãs (julho e agosto). Não foram observadas diferenças significativas no desem-penho das rãs para as diferentes densidades. A utilização de 200 tilápias por viveiro melhorou o ganho de peso dos peixes e a concentração de oxigênio dissolvido da água, comparado com a densidade de 300 peixes por viveiro. Este novo sistema de criação proporcionou um ambiente adequado para as rãs com ganho de peso e ausência de mortalidade durante o inverno.
Raising bullfrogs (Rana catesbeiana) in cages placed in tilapia ponds
Keywords: Frog raising; Ranicultura